2008
DOI: 10.1097/ta.0b013e31805824f3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Screw Fixation Without Bone Graft for Cystic-Type Scaphoid Fractures

Abstract: designing a treatment strategy, so we expanded this classification system to acute scaphoid fractures (Fig. 1). The purpose of this study is to explain our treatment strategy based to our new classification system for scaphoid fractures and to demonstrate that bone graft is not necessary for cystic type fractures. PATIENTS AND METHODSWe retrospectively studied the 105 scaphoid fractures (Table 1) of 94 male and 11 female patients ranging in age from 14 to 67 years (average, 26 years). The radiograms were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Particularly for our inquiry, this can only be compared to clinically found fractures to a limited extent, since it does not offer interlocking fragments, which can result in a certain blocking effect against rotation even in simple compression screw treatment. By using a linear osteotomy in cadaver scaphoids on the other hand, we did not evaluate the effect of comminution, oblique fractures, not completely reduced fractures, cystic type fractures [ 28 ], interpositional bonegrafting [ 24 ] or cartilage interposition which may decrease the general stability of the fracture in the in vivo situation.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Particularly for our inquiry, this can only be compared to clinically found fractures to a limited extent, since it does not offer interlocking fragments, which can result in a certain blocking effect against rotation even in simple compression screw treatment. By using a linear osteotomy in cadaver scaphoids on the other hand, we did not evaluate the effect of comminution, oblique fractures, not completely reduced fractures, cystic type fractures [ 28 ], interpositional bonegrafting [ 24 ] or cartilage interposition which may decrease the general stability of the fracture in the in vivo situation.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…7,8,15,24,25 Many techniques have been described, but the optimal treatment of scaphoid nonunion continues to be debated. 4,7,13,24,26,27 Union rates for this technique have been reported as high as 100%. Authors recommend grafting to compensate for bone loss, correct scaphoid deformity, restore normal wrist kinematics, facilitate screw placement, and induce osteogenic signaling.…”
Section: Rationale For Treatmentmentioning
confidence: 97%
“…6,14 Several authors have suggested that stable, well-aligned and vascular nonunions require only rigid fixation to achieve union. 13,14,26 In much the same way that cannulated headless compression screws have expanded surgical indications to include even nondisplaced acute scaphoid fractures by simplifying the procedure and making it less invasive, several authors 2e6 have found that this minimally invasive approach may also translate into certain established scaphoid fracture nonunions.…”
Section: Rationale For Screw Fixation Alonementioning
confidence: 99%
“…7) We reported Ikeda's classification (Fig. 2), 8) which did not consider the time interval between injury and treatment, was based on radiographic findings and proposed a specific treatment strategy.…”
Section: Overviewmentioning
confidence: 99%
“…7) We reported Ikeda's classification (Fig. 2), 8) which did not consider the time interval between injury and treatment, was based on radiographic findings and proposed a specific treatment strategy.Scaphoid fractures have a tendency for nonunion due to the nature of intraarticular fracture and vulnerable vascularity of the proximal fragments. 9) Moreover, the clinical problem is that some patients do not seek medical assistance at the time of injury and some fractures are not recognized on initial radiographs.…”
mentioning
confidence: 99%